Social Media Exposure and Usage of Cyber Slang: Bases in Examining the Academic Writing Conventions of the Students (Shanti Journal, 2022)
The study established the relation of social media exposure and cyber slang usage towards the academic writing conventions of the Grade ten students of Kumalarang National High School, Kumalarang Zamboanga del Sur, Philippines. The study has been conducted in the second semester of the school year 2020-2021 and has utilized the descriptive statistics such as percentage, weighted mean as a measure of average, and standard deviation as a measure of variability of numerical observations in order to determine the levels of the students’ exposure to social media, cyber slang, and academic writing conventions. Fifty (50) respondents coming from the aforementioned grade have been distributed with online survey questionnaires based on the concept of several references related to this study. The study found that the Grade 10 students of Kumalarang National High School held the high level of exposure in social media, and usage of cyber slang in social media; and their overall writing convention has a descriptive equivalent of average. The results of the study justified the following; there is no significant relationship between students’ social media exposure and cyber slang usage, there is no significant relationship between exposure to social media and students’ academic writing conventions, and there is no significant relationship between cyber slang usage and students’ academic writing conventions. The result of the study also signified that even if the students are exposed to social media, yet their use of cyber slang is still controlled. The more they used cyber slang in social media, their academic writing conventions will also increase. Further, the results of the study implied that social media exposure contributes a lot to students’ academic writing conventions. Besides it supplied notable entertainment, this can also be a communication channel at their most convenient time, pace and location that teachers cannot afford to overlook. The possibilities to acquire learning with variety of data in social media has reinforced and influenced students’ academic writing conventions. Even if cyber slang is already part of human’s lives in the modern century, yet this will academically challenge the students to decide as to what form of writing they are going to use in order to fit in the requirements both in school and in the community. With this, students must know how to set limit as to when and when not to use them. By knowing this fact, they may widen their competency in the field of writing without sacrificing the English language. This will also allow them to establish their voice in writing.